Current drug therapy and pharmaceutical challenges for Chagas disease - Bermudez, Jose Maria (2016)
One of the most significant health problems in the American continent in terms of human health, and socioeconomic impact is Chagas disease, caused by the protozoan parasite Trypanosoma cruzi. Infection was originally transmitted by reduviid insects, congenitally from mother to fetus, and by oral ingestion in sylvatic/rural environments, but blood transfusions, organ transplants, laboratory accidents, and sharing of contaminated syringes also contribute to modern day transmission. Likewise, Chagas disease used to be endemic from Northern Mexico to Argentina, but migrations have earned it global. The parasite has a complex life cycle, infecting different species, and invading a variety of cells - including muscle and nerve cells of the heart and gastrointestinal tract - in the mammalian host. Human infection outcome is a potentially fatal cardiomyopathy, and gastrointestinal tract lesions. In absence of a vaccine, vector control and treatment of patients are the only tools to control the disease. Unfortunately, the only drugs now available for Chagas' disease, Nifurtimox and Benznidazole, are relatively toxic for adult patients, and require prolonged administration. Benznidazole is the first choice for Chagas disease treatment due to its lower side effects than Nifurtimox. However, different strategies are being sought to overcome Benznidazole's toxicity including shorter or intermittent administration schedules-either alone or in combination with other drugs. In addition, a long list of compounds has shown trypanocidal activity, ranging from natural products to specially designed molecules, re-purposing drugs commercialized to treat other maladies, and homeopathy. In the present review, we will briefly summarize the upturns of current treatment of Chagas disease, discuss the increment on research and scientific publications about this topic, and give an overview of the state-of-the-art research aiming to produce an alternative medication to treat T. cruzi infection.